Executive Committee Minutes 2015-09-10 - Academic Senate:::::::::
Agenda approved. Minutes of 9/10 approved. Chair Report. President Report. Vice Chair Report. Vice President of Administration and Finance Report. SAC Report. EPC Report. FSAC Report. Associated Students Report. Follow up on call for GMC Faculty Vision workgroup. Implementation of Constitutional Referendum. Discussion about APC. Executive Committee Social. Senate agenda approved.